A brief welcome to the universe a pocket-sized tour - Tyson, Neil deGrasse (Princeton University Press, 2021)
"This is a condensed edition of Welcome to the Universe - essentially a pocket-sized version of the original "astrophysical tour" of the cosmos. In 8 chapters (compared to the original 24 chapters), the reader learns the essential astrophysics everyone should know -- about the size and scale of the universe; the solar system; the lives/deaths of stars; the search for life in the galaxy; our Milky Way; galaxies, the Big Bang and the expanding universe; inflation and the multiverse; and our future in the cosmos. For those who may have felt that Welcome to the Universe was a bit beyond them, this book covers all the essentials in an even more accessible and concise fashion, while imparting real physical insight into how the universe works by the book's end"--